2012
DOI: 10.1007/s00535-012-0675-z
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib induces tumor-specific cell death and growth inhibition in hepatocellular carcinoma and improves liver fibrosis

Abstract: Bortezomib appears to be an ideal target drug for HCC with LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
1
30
1
Order By: Relevance
“…For example, bortezomib prevents bleomycin-induced experimental dermal fibrosis in mice (15). In addition, bortezomib ameliorated liver fibrosis with a significant reduction of the α-smooth muscle actin expression in a N-nitrosodiethylamine-induced liver fibrosis rat model (16). In a renal in vitro investigation, MG132 (an experimental proteasome inhibiting agent) blocked the TGFβ-induced transformation of renal fibroblast NRK49F cells to myofibroblast cells (17), which express extracellular matrix and α-smooth muscle actin and play a key role in the progression of renal fibrosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, bortezomib prevents bleomycin-induced experimental dermal fibrosis in mice (15). In addition, bortezomib ameliorated liver fibrosis with a significant reduction of the α-smooth muscle actin expression in a N-nitrosodiethylamine-induced liver fibrosis rat model (16). In a renal in vitro investigation, MG132 (an experimental proteasome inhibiting agent) blocked the TGFβ-induced transformation of renal fibroblast NRK49F cells to myofibroblast cells (17), which express extracellular matrix and α-smooth muscle actin and play a key role in the progression of renal fibrosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…It can promote cell apoptosis [80,81] by reducing p-Akt levels [82][83][84] and inducing autophagy via proteasome independent mechanisms [85]. BZB was also shown to suppress HCC cell proliferation by increasing the levels of cell cycle inhibitors p27/p21 [79,86,87], and reducing the levels of cyclin D1 [87,88], the phosphorylated form of pRB, and the transcription factor E2F1 [87][88][89][90].…”
Section: Bortezomibmentioning
confidence: 96%
“…Proteasome inhibition could represent a novel therapeutic strategy for advanced HCC [5,7]. The nextgeneration orally bio-available irreversible proteasome inhibitor oprozomib (OZ) is assumed to evoke fewer adverse events and improve antitumor activity compared to the first-in-class proteasome inhibitor bortezomib [3].…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomibinduced cell death is related to induction of endoplasmic reticulum (ER) stress, inhibition of nuclear factor kappa B, activation of caspase-8 and generation of oxidative stress [3,4]. Multiple clinical trials have demonstrated that this small-molecule possesses antitumor activity in a variety of human cancers [5,6]. Despite promising preclinical results [5], a multicenter single-arm phase II trial assessing the activity of bortezomib in HCC has demonstrated modest antitumor effects, indicating intrinsic or acquired resistance [4,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation